When COVID-19 struck the world and elite sports: Psychological challenges and support provision in five countries during the first phase of the pandemic - Lundqvist, C.; Macdougall, H.; Noguchi, Y.; Malherbe, A. (Journal of Sport Psychology in Action, 2021)
The authors were operating in professional roles related to preparations for Tokyo 2020 when the COVID-19 pandemic changed the world. The purpose of the article is to share applied experiences and personal reflections from different parts of the world of psychological challenges and support strategies adopted in elite sports during the first phase of the pandemic. The article focuses on the period between March-August 2020. Common themes experienced across countries included motivational issues, stress and anxiety, loss of routine, life balance challenges, but also benefits for some athletes of extended preparation time and recovery. Variations in support strategies and consequences from the effects of COVID-19 occurred across countries, sports, and staff and athlete roles in elite sports.